Pomegranate 2022
DOI: 10.5772/intechopen.97188
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pomegranate in the Management of Cancer

Abstract: Pomegranate (Punica granatum) has been used since ages as a folk medicine. Studies have shown that pomegranate extracts have a role in various signaling pathways involved in inflammation, cellular transformation, hyperproliferation, angiogenesis, initiation of tumorigenesis, and eventually suppressing the final steps of tumorigenesis and metastasis. In this chapter, we have discussed some of the polyphenolic constituents present in pomegranate and their medical value, and we then discussed studies on chemoprev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Because it contains a significant number of hydrolyzable tannins and anthocyanins, pomegranate possesses potent antioxidant and anti-inflammatory properties (Singh et al, 2023). Several studies have demonstrated that the pomegranate extract (PE), seeds, and juice exerts anti-cancer potential by altering several key signaling pathways controlling cell division and proliferation (Malik et al, 2005;Adhami et al, 2009;Turrini et al, 2015;Amulya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Because it contains a significant number of hydrolyzable tannins and anthocyanins, pomegranate possesses potent antioxidant and anti-inflammatory properties (Singh et al, 2023). Several studies have demonstrated that the pomegranate extract (PE), seeds, and juice exerts anti-cancer potential by altering several key signaling pathways controlling cell division and proliferation (Malik et al, 2005;Adhami et al, 2009;Turrini et al, 2015;Amulya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%